The Gap in Legal Protection Between Permanent Employees and Contract Workers in Indonesia - Klaudine Shyne Hendriko (Media Hukum Indonesia (MHI), 2026)
Legal protection for workers represents a form of the state's responsibility in ensuring the fulfillment of citizens’ constitutional rights as stipulated in the 1945 Constitution of the Republic of Indonesia. In employment practices in Indonesia, there are permanent employees and contract employees who have different legal statuses and levels of protection. These differences in status create disparities in the implementation of workers’ normative rights, particularly regarding job security, protection against termination of employment, and workers’ welfare. This article aims to analyze the regulation of legal protection for permanent employees and contract employees and to examine the forms of disparities in legal protection between them. The results of the discussion indicate that although legal protection for workers has been regulated in various laws and regulations, in practice contract employees remain in a more vulnerable position compared to permanent employees. Therefore, strengthening supervision and optimizing the implementation of labor regulations are necessary.